Palembang City Web-Based Futsal Field Rental System Using Express JS and React JS - Apriansyah, Apriansyah (Jurusan Informatika Universitas Tanjungpura, 2024)
Futsal is one of the most popular sports for almost all ages in the city of Palembang. At this time the process of ordering the futsal field is still being carried out through prospective tenants having to come directly to the field provider's place which can take time and get invalid information regarding the field to be ordered, so there is a need for a system that can provide information and manage futsal field data to get what is expected. In the current era of digitalization, the ease of obtaining information greatly affects performance in any field, therefore in this study, the authors built a system that can facilitate ordering and rental of Web-based Futsal Fields in Palembang City using Express JS and React JS. This system was developed using the prototype method, prototype is an approach in developing software or systems with several steps in this method, namely identifying user needs, designing prototypes based on needs, building prototypes, evaluating tests, refining and iteration, and developing final products.